2007
DOI: 10.1021/bk-2007-0968.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Bitumen in Neolithic Iran: Biomolecular and Isotopic Evidence

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Sixty‐five pottery fragments (Table 1) from nine Neolithic sites in the Fertile Crescent were assembled for microwave‐assisted solvent extraction as part of a research project examining the early uses of pottery in the Middle East (Gregg 2003, in press; Gregg et al. 2007, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty‐five pottery fragments (Table 1) from nine Neolithic sites in the Fertile Crescent were assembled for microwave‐assisted solvent extraction as part of a research project examining the early uses of pottery in the Middle East (Gregg 2003, in press; Gregg et al. 2007, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…As part of a wider study of the initial development and use of pottery in the Middle East (Gregg 2003, in press; Gregg et al. 2007, 2009), one of the current authors (MWG) attempted to extract organic residues from 231 pottery fragments from 18 early agricultural villages or pastoral encampments in the Middle East using the ‘conventional’ solvent extraction (DCM:MeOH, 2:1, v/v) and BSTFA derivatization techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many of these techniques have proven successful in the recovery and identification of organic residues from different archaeological contexts in many regions, 20 years of intensive research have shown that unique molecular biomarkers or diagnostic distributions of longer carbon chain compounds are rarely preserved at archaeological sites for more than 2 or 3,000 years (Heron et al, 1994;Boëda et al, 1996;Connan et al, 2004;Mirabaud et al, 2007;Gregg et al, 2007). It is suspected that the delayed decomposition of lipids within archaeological pottery is due to their being absorbed into the clay fabric of vessels (Evershed et al, 1990;Heron et al, 1991), but diagnostic long carbon chain molecules survive only under exceptional circumstances, such as the anaerobic conditions at the submerged fourth millennium BCE site at Clairvaux XIV in the French Jura (Mirabaud et al, 2007) or the continuously desiccated 18th dynasty Egyptian capital at Amarna (Stern et al, 2000).…”
Section: Bibliography Introductionmentioning
confidence: 99%
“…It is suspected that the delayed decomposition of lipids within archaeological pottery is due to their being absorbed into the clay fabric of vessels (Evershed et al, 1990;Heron et al, 1991), but diagnostic long carbon chain molecules survive only under exceptional circumstances, such as the anaerobic conditions at the submerged fourth millennium BCE site at Clairvaux XIV in the French Jura (Mirabaud et al, 2007) or the continuously desiccated 18th dynasty Egyptian capital at Amarna (Stern et al, 2000). Bitumen appears to be the one notable exception, with extant molecular signatures having been identified in pottery vessels from 8th millennium BCE sites in southern Mesopotamia (Connan et al, 2004;Gregg et al, 2007) and on the surface of 40,000-year-old Middle Paleolithic tools from northern Syria (Boëda et al, 1996). Robert White's Principles and Practice of Soil Science (2006) provides a useful guide to the physical and chemical process involved in biodegradation of organic compounds under different soil and climatic conditions.…”
Section: Bibliography Introductionmentioning
confidence: 99%